Positive Impact of The Covid-19 Pandemic on The World of Education - Abu Muna Almaududi Ausat (Jurnal Pendidikan, 2022)
The Covid-19 pandemic, which has disrupted the order of life in the world of education, is still ongoing; various efforts are being made to end the pandemic period as soon as possible. Even in the midst of a pandemic, the world of education must be given special attention in order to avoid being negatively impacted. The opportunity to advance the world of education through online learning is a solution to meet educational standards through the use of information technology so that students and teachers are interconnected and the teaching and learning process can still be carried out properly through the use of technology. The method used in this study is qualitative, with approach content analysis and descriptive presentation. As a source of research data, the author examines documents in the form of text, news, journals, and newspapers. Although the pandemic had many negative consequences, it had a positive impact on the world of education. This positive impact can inspire the community to persevere in the face of adversity in order to achieve more advanced educational goals. Among the many positive effects of online learning during the Covid-19 pandemic, one has the greatest impact on the world of education: it accelerates educational transformation.